Revisiting China's Competition Law and Its Interaction with Intellectual Property Rights - Li, Guangjie (Munich Intellectual Property Law Center - MIPLC, 2018)
Taking the dynamics of EU competition policy as a reference, the author provides a historical perspective of China's competition law, enforcement mechanisms and future challenges against the background of ongoing economic reforms and the concomitant modernisation of the judicial system. Readers are familiarised with the main principles of China